2022
DOI: 10.1039/d1tc05180f
|View full text |Cite
|
Sign up to set email alerts
|

FeV3O8/MoS2 nanostructure heterojunctions as a highly effective electrocatalyst for hydrogen evolution

Abstract: Great efforts have been made to explore efficient, stable and resource-rich non-noble metal electrocatalysts instead of noble metal electrocatalysts for the hydrogen evolution reaction (HER).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 67 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…Especially, transition-metal oxides (TMOs) display particularly high catalytic activity and remarkable ability to withstand alkaline conditions. 39 The bimetallic oxide catalysts can possibly change the electronic structures of these catalysts by modulating the compositions as well as the physical and chemical properties of the metals. 40 It is believed that bimetallic compounds provide rich active sites, captivating inert sites and simultaneously increasing conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, transition-metal oxides (TMOs) display particularly high catalytic activity and remarkable ability to withstand alkaline conditions. 39 The bimetallic oxide catalysts can possibly change the electronic structures of these catalysts by modulating the compositions as well as the physical and chemical properties of the metals. 40 It is believed that bimetallic compounds provide rich active sites, captivating inert sites and simultaneously increasing conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, improving the catalytic activity of these materials remains a significant challenge due to their poor electrical conductivity. , In recent years, numerous research studies have demonstrated the excellent electrocatalytic properties of transition-metal-based compounds. Especially, transition-metal oxides (TMOs) display particularly high catalytic activity and remarkable ability to withstand alkaline conditions . The bimetallic oxide catalysts can possibly change the electronic structures of these catalysts by modulating the compositions as well as the physical and chemical properties of the metals .…”
Section: Introductionmentioning
confidence: 99%
“…The signal peaks of FeV 3 O 8 /RGO observed at 200–300 and 645 cm –1 were related to the nonequivalent and stretching vibrations of Fe–O. Signal peaks of 350–500 and 820 cm –1 were assigned to the stretching bands of V–O–V and V–O–e, respectively. , The Raman spectrum region at around 619 cm –1 was attributed to the xanthene ring puckering bonds, while the region from 1195 to 1644 cm –1 in the spectrum was assigned to C–C, C–H, and CC stretching of RB in RB/RGO and FeV 3 O 8 -RB/RGO. , TGA tests for FeV 3 O 8 /RGO and FeV 3 O 8 -RB/RGO were performed, as shown in Figure S6b. The weight loss values of about 5 and 7% at 270 and 395 °C in FeV 3 O 8 /RGO, respectively, were related to the absence of the crystal water and the carbonization of RGO.…”
Section: Resultsmentioning
confidence: 92%
“…The hydrogen evolution reaction (HER) is a key reaction in energy conversion applications such as renewable energy and hydrogen fuel cells. [1][2][3][4][5] Pt is currently considered to be the best HER electrocatalyst, but its low abundance, high cost, low utilization rate, and limited stability limit its development. [6][7][8][9][10] Reducing the amount of Pt and improving the catalytic activity can be achieved by combining Pt with transition metals (such as Ni, 11 W, 12 Ti, 13 Mo, 14 Fe, 15 and Te 16 ).…”
Section: Introductionmentioning
confidence: 99%